Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

What is the result of subtracting the second equation from the first? \begin{aligned} -3x+2y &= 7 \\\\ -3x-2y &= 4 \end{aligned} −3x

Home/Math/What is the result of subtracting the second equation from the first? \begin{aligned} -3x+2y &= 7 \\\\ -3x-2y &= 4 \end{aligned} −3x

What is the result of subtracting the second equation from the first? \begin{aligned} -3x+2y &= 7 \\\\ -3x-2y &= 4 \end{aligned} −3x

Question

What is the result of subtracting the second equation from the first? \begin{aligned} -3x+2y &= 7 \\\\ -3x-2y &= 4 \end{aligned} −3x+2y −3x−2y =7 =4

## Answers ( )

Answer:

y = 3/4

Step-by-step explanation:

Given two equations

-3x+2y = 7 … (1)

-3x-2y = 4 … (2)

Subtracting the second equation from the first will give us;

-3x-(-3x)-2y-(+2y) = 4-7

-3x+3x-2y-2y = -3

-2y-2y = -3

-4y = -3

y = 3/4

The result of the difference between the second and the first will give y = 3/4